If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 = 3(n + 2) + 1 Reorder the terms: 19 = 3(2 + n) + 1 19 = (2 * 3 + n * 3) + 1 19 = (6 + 3n) + 1 Reorder the terms: 19 = 6 + 1 + 3n Combine like terms: 6 + 1 = 7 19 = 7 + 3n Solving 19 = 7 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 19 + -3n = 7 + 3n + -3n Combine like terms: 3n + -3n = 0 19 + -3n = 7 + 0 19 + -3n = 7 Add '-19' to each side of the equation. 19 + -19 + -3n = 7 + -19 Combine like terms: 19 + -19 = 0 0 + -3n = 7 + -19 -3n = 7 + -19 Combine like terms: 7 + -19 = -12 -3n = -12 Divide each side by '-3'. n = 4 Simplifying n = 4
| (2x-3)=(x+16) | | 15x-2x+3=10 | | 3p+8-7p= | | -7(5x+5)+4x=3x | | 7y-x=9 | | .024a-8=.224a+2 | | 3(m-8)+-2=8 | | 6x+35=8x+15 | | 8t+2m=w-8 | | -22+t=36 | | -4(2t+2)=-32 | | -4(-6x+1)-3x=1 | | 25z-15=6z-14 | | .03x-3.9=.66 | | 7x+3x=5x+50 | | 8x+8-6x=-6 | | 25z-15=6z-24 | | 4=2(g-11)-2 | | (-7p)3= | | 2=7x-26 | | 15-g=6 | | -6+3(-8x+1)=15 | | 3(f-8)=-24 | | .04m=.08 | | 5t(10-3t)= | | 7/x-4=14/6 | | -5(4x-1)=-3x-6 | | 7-k=5 | | -7x-13+9x-19=-4 | | -1=2(j-8)+1 | | 10(s-6)=-146 | | 32-4x=18-6x |